Revisiting Religious Education: The Shifting Curve of Short-Run Aggregate Supply of Human Resource in Educational Capitalism - Stimson Hutagalung; Halim Wiryadinata; Suwarto Adi; Alvyn Cesarianto Hendriks (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
Education is understood as the institution creating human resources capable of making a better society in facing social change. However, education becomes the object of social change when education must submit to the development of the industrial world. The hidden curriculum is taught to prepare human resources to fulfil the market’s needs. Education is prepared to work for people who have capital as known terminology, capitalism. The growth of technology and its equipment make education a private and expensive institution economically, whereas unfortunate people cannot participate. Therefore, it creates incapable human resources to fill the free-market vacancy, and religious education is placed in the midpoint. The inequality of supply in human resource skills towards the demand for working space forms the unstable demand and supply curves. As a result, the shifting curve of the Short-Run Aggregate Supply of human capital moves toward supporting capitalism to stand still. Through the sociological approach, the perspective emic discovers the problematic fundamental for religious education is facing a social change. The dilemma of religious education leads to legitimate the path of capitalism in the education area (or market). The result revisits religious education to bring the equilibrium point between the product and the quality of human resources in a new form of academic capitalism by transferring religious values based on local wisdom and integrating curriculum between religious and non-religious subjects.